Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Persamaan Kuadrat Berdasarkan Teori Polya - Husnul; Rayhana; A. Sriyanti; Suharti (Alauddin Journal of Mathematics Education, 2024)
This study aims to describe student errors and analyze the factors causing student errors in solving quadratic equation problems. This type of research is descriptive qualitative. The subjects used in this study were class IX A consisting of 16 students, then 3 students were selected based on their high, medium, and low category abilities obtained after being given test questions. The instrument used was a test instrument in the form of two questions that met the Polya theory indicators. The results of this study indicate that there are four errors in solving quadratic equation problems: (1) errors in understanding the problem, namely not being able to write down information related to the problem that is known in the problem; (2) errors in making plans, namely not being able to change the problem sentence into a mathematical model and errors in choosing the steps for solving, (3) errors in implementing the plan, namely errors in writing the final answer, (4) not mastering the concept of arithmetic operations and rechecking the answers. Factors causing student errors in understanding are students' lack of understanding of the concept, difficulty in mathematical modeling, and students' lack of thoroughness in arithmetic skills.